Comparative study between Arabic language textbooks published by Toha Putra and Tiga Serangkai for junior high school students in the 2013 curriculum based on national education standards - Ainul Mardhiyah (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2025)
The background to this research is that textbooks are a medium for realizing learning objectives. Textbooks are teaching materials that play an important role in the learning process. The aim of this research is to determine the quality of Arabic textbooks published by Toha Putra and Tiga Serangkai. The sample in this research was an Arabic language textbook for class VIII junior high school students. Data collection techniques are conducting literature studies, processing data, presenting data and providing interpretation. Data analysis uses qualitative data analysis techniques. The research results are as follows: Books published by Toha Putra show content quality of 91.67%, presentation of 79.16%, language of 75%, and graphics of 94%. Meanwhile, books published by Tiga Serangkai show content quality of 95.83%, presentation of 81.94%, language of 100%, and graphics of 93.51%. Based on the comparison carried out on each component of textbook suitability, the book published by Toha Putra is only superior in the graphic aspect. Meanwhile, for the other three aspects (content, presentation, and language), the textbooks published by the triad are superior to the Toha Putra textbooks. In general, the overall percentage of the two textbooks is the textbook published by Toha Putra 89.29% (very good), and the textbook published by Tiga Serangkai 92.34% (Excellent).